The epic fragment in mid sixteenth-century French poetry - Braybrook, J; Braybrook, J. (1981)
﻿ This study aims to produce a positive assessment of the Franciade, by viewing Ronsard's epic venture in the context of works by Ronsard himself and by poets such as Baïf and Belleau. The com- positions considered extract single episodes from an epic whole, and are united by their structural and rhetorical techniques, forming a group dominated by the Franciade. The first chapter examines the question of genre raised by the fragments, and reviews classical models utilized by the French poets, placing particular emphasis upon the Alexandrians. It re- veals how the sixteenth-century poets long to produce a full-scale epic . Chapter 2 groups the fragments according to theme, highlighting Argonautic poems, notably Ronsard's Hymne de Calais, et de Zetes, Hymne de Pollux et de Castor, and Hylas. Chapter 3 examines the structure of the fragments in terms of contraction and expansion. Some poets circumscribe their material with a prelude and conclusion; others extend its temporal and spatial perspectives, by such means as retrospection, prophecy, and descriptions of ornate objects. The rhetoric of the fragments is seen in Chapter 4 to reflect the expansive urge: simile, circumlocution, and preterition all widen the poetic vistas. Chapter 5 studies Ronsard's approach to the problem of inven- ting an original framework for his epic, how he tries to lend it coherence by structural and rhetorical means. Yet the techniques Ronsard practised in the fragments finally prevail: the Franciade breaks up into a series of vivid miniatures: Ronsard repeatedly returns to material made familiar by classical epics. The conclusion emphasizes that the 'accidental' fragmentation of the Franciade should be viewed alongside the voluntary frag- mentation of the sixteenth-century heroic miniatures. The Franciade should, especially, be considered in conjunction with other Ron- sardian productions, such as the Argonautic hymns. Together with these, it forms an intricate fretwork of epic motifs.